2017
DOI: 10.1093/mnras/stx279
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spatial fluctuations in the extragalactic background light on hard gamma-ray spectra

Abstract: This study investigates the impact of the fluctuations in the extra galactic background light (EBL) on the attenuation of the hard γ-ray spectra of distant blazars. EBL fluctuations occur on the scales up to 100 Mpc and are caused by clustering of galaxies. The EBL photons interact with high energy γ-rays via the electron-positron pair production mechanism: γ + γ ′ → e + + e − . The attenuation of γ-rays depends on their energy and the density of the intervening EBL photon field. Using a simple model for the e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
(37 reference statements)
2
5
0
Order By: Relevance
“…For the homogeneous EBL background (beyond 50 Mpc) we use our previous EBL forward model KF17 (Kudoda & Faltenbacher 2017), considering only the contribution form main-sequence stars to the EBL stellar component. The EBL at z = z1 is derived by integrating the contributions from stars of all masses formed throughout the history of the universe from z = 10 to z = z1.…”
Section: The Homogeneous Ebl Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…For the homogeneous EBL background (beyond 50 Mpc) we use our previous EBL forward model KF17 (Kudoda & Faltenbacher 2017), considering only the contribution form main-sequence stars to the EBL stellar component. The EBL at z = z1 is derived by integrating the contributions from stars of all masses formed throughout the history of the universe from z = 10 to z = z1.…”
Section: The Homogeneous Ebl Backgroundmentioning
confidence: 99%
“…Backward evolution models begin with the observed present day luminosity functions for galaxy populations in the local Universe and extrapolate them to higher redshift (e.g., Malkan & Stecker 1998;Rowan-Robinson 2001;Stecker et al 2006). Forward evolution models start with early structure formation scenarios to predict the galactic evolution forward in time (e.g., Dwek et al 1998;Razzaque et al 2009;Finke et al 2010;Kudoda & Faltenbacher 2017). Cosmic chemical evolution models consider basic galaxy ingredients such as gas, metallicity and radiation content and follow their evolution in a large comoving volume element (e.g., Pei & Fall 1995;Pei et al 1999).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Observation of the blazars by the large area telescope (LAT) onboard the Fermi satellite in energy range from 30 MeV to more than 500 GeV provides a very strong observational evidence regarding the intrinsic MeV-GeV emission from them [29]. Combined MeV-GeV and TeV observations have provided a new tool to constrain the EBL intensity [30,31,32,33,34,35,36,37]. Recently, the Fermi-LAT observations have been used to indirectly measure the EBL from the absorption features seen in the γ-ray spectra of blazars beyond the redshift z > 1 [38,39].…”
Section: Introductionmentioning
confidence: 99%
“…While the statistical significance of these two indications is still modest due to a limited sample used in F15 (∼2.5σ ), these effects are in line with other deviations from the absorption-only model that neglects secondary emission from electron-positron pairs produced by primary very high energy (VHE, E >100 GeV) γ-rays. It was shown that EBL fluctuations are not strong enough to account for such an effect (F15, [12]- [13]). In this paper we present an astrophysical interpretation of the effects considered by F15 in the framework of the intergalactic electromagnetic cascade model [14] (hereafter D17).…”
Section: Introductionmentioning
confidence: 99%